Optimasi Pertumbuhan Lidah Buaya dengan Pupuk NPK Phonska dalam Metode Polybag di Kelompok PKK RT 23, Pasir Putih, Kota Jambi - Nasution, Hasriati; Yusfaneti; Saat, Asmadi (WIDA Publishing, 2024)
Aloe vera plants have thick flesh rich in active substances such as folic acid, choline, vitamins A, C, B12, E, and various minerals like calcium, potassium, magnesium, and sodium. The application of NPK Phonska fertilizer can enhance the growth and greenery of aloe vera leaves, as well as stimulate root growth and the formation of plant offspring. The objective of this community service is to improve the skills of the PKK (Family Welfare Movement) group of RT 23 in Pasir Putih Subdistrict, Jambi City, in cultivating aloe vera by providing guidance on the application of NPK Phonska fertilizer. This service is conducted in two stages: providing material on NPK Phonska fertilization and conducting a demonstration on planting aloe vera using polybags. The service team provides materials such as aloe vera seedlings, NPK Phonska fertilizer, polybags, soil media, and agricultural tools. The results show high enthusiasm and understanding from the PKK group members regarding the application of NPK Phonska fertilizer for aloe vera growth. It is hoped that through this guidance, their skills in caring for aloe vera plants will improve, resulting in lush growth with shiny green leaves and abundant offspring formation.